Lust - Zitaki, Maria; Tsiachristas, Giannis (Greece, 2017)
The documentary tells the story of Rahmat refugee from Afghanistan who works as a translator in the camp of Eleonas. The film through the history of Rahmat deals with aspects of the daily life of refugees and the problems they face in Greece.
Verzio Film Festival Submission
Keywords: Documentary films